Infecção por Ehrlichia sp. em equídeos e carrapatos na região Centro-Oeste, Brasil - Muraro, Lívia Saab (2021)
The present study investigated the presence of Ehrlichia spp. in horses and ticks from properties located in the municipalities of Poxoréu, Poconé and Ranchos in Cuiabá located in the State of Mato Grosso, and in a ranch in the municipality of Corumbá located in the State of Mato Grosso do Sul, by determining the molecular, serological and risk factors associated with infection by Ehrlichia spp. The samples that were evaluated were 148 equidae in the State of Mato Grosso and 12 horses in Mato Grosso do Sul. All Blood and ticks that were collected, which were evaluated by the Polymerase Chain Reaction (PCR) to amplify partial fragments of the dsb gene and 16S ehrlichial rRNA. The samples serum was also evaluated by means of the Indirect Immunofluorescence Reaction (IFA) to detect anti-Ehrlichia spp. using Ehrlichia canis crude antigens. Possible clinical and hematological associations were assessed with the results of PCR and IFA for Chi-square or Fisher's exact test. Of the samples from Mato Grosso, 3 (2.07%) horses presented fragments of the dsb gene, whose amplification products were similar to E. minasensis sequences deposited on the GenBank. Sixty-one (41.2%) horses reacted at the IFA with titers ranging from 40 to 2560. Serum reactivity against E. canis antigens was associated with tick parasitism, rural origin, hypoalbuminemia and hyperproteinemia (p≤0.05). A total of 901 specimens of ticks were removed from these animals and later identified as D. nitens, A. sculptum and R. microplus. The tick DNA was extracted and subjected to the same PCR assays to detect Ehrlichia spp, and all were negative. Of the samples from the state of Mato Grosso do Sul, the horse DNA samples did not show amplification in the PCRs and five of them were seroreagent (41.7%) with titers ranging from 40 to 160. The total of 57 tick specimens that were removed from these animals and identified as D. nitens, A. sculptum and R. microplus, and an adult female of A. sculptum showed amplified fragments of the dsb and 16S rRNA genes for Ehrlichia. The present work identified for the first time evidence of the natural infection of Ehrlichia minasensis in horses from Mato Grosso, and also in tick Amblyomma sculptum from the Pantanal of Mato Grosso do Sul, species of Ehrlichia sp. close to strains detected in wild mammals in Brazil and Argentina.